A Methyl Parathion Recognition Method Based on Carbon Nitride Incorporated Hexagonal Boron Nitride Nanosheets Composite Including Molecularly Imprinted Polymer. Issue 12 (9th July 2019) - Kıran, Tuğba Raika; Atar, Necip; Yola, Mehmet Lütfi
Abstract : Methyl parathion (MP) is an organophosphate chemical agent. Due to low solubility and bioaccumulation, it results in serious health problems. Electrochemical recognition based on graphitic carbon nitride (CN) incorporated hexagonal boron nitride (HBN) nanosheets and molecularly imprinted polymer (MIP) was presented for methyl parathion (MP) detection. Scanning electron microscopy (SEM), X-ray diffraction (XRD) method, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were utilized for characterizations. After that, MP imprinted voltammetric sensor on CN-HBN nanocomposite was carried out in the presence of 100.0 mM pyrrole containing 25.0 mM MP via CV. 1.0 × 10 −12 –2.0 × 10 −9 M and 2.0 × 10 −13 M were found as the linearity range and the detection limit (LOD). Finally, MP imprinted sensor was applied to orange juice samples for MP analysis.